2016
DOI: 10.18632/oncotarget.10255
|View full text |Cite
|
Sign up to set email alerts
|

What might explain deprivation-specific differences in the excess hazard of breast cancer death amongst screen-detected women? Analysis of patients diagnosed in the West Midlands region of England from 1989 to 2011

Abstract: BackgroundBreast cancer survival is higher in less deprived women, even amongst women whose tumor was screen-detected, but reasons behind this have not been comprehensively investigated.MethodsThe excess hazard of breast cancer death in 20,265 women diagnosed with breast cancer, followed up to 2012, was estimated for screen-detected and non-screen-detected women, comparing more deprived to less deprived women using flexible parametric models. Models were adjusted for individual and tumor factors, treatment rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“… 78 , 79 These studies assessed the following cancers: female breast, 8 , 9 , 13 , 17 , 18 , 26 , 29 , 30 , 32 , 36 , 44 , 49 , 53 , 59 - 61 , 65 , 67 , 77 male breast, 58 cervix, 24 , 50 ovary, 23 , 42 , 45 endometrium, 33 prostate, 7 , 34 , 43 , 64 penis, 47 colorectum, 12 , 15 , 22 , 28 , 40 , 48 , 55 , 57 , 66 , 73 lung, 10 , 11 , 16 , 20 , 25 , 41 , 56 head and neck, 31 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 78 , 79 These studies assessed the following cancers: female breast, 8 , 9 , 13 , 17 , 18 , 26 , 29 , 30 , 32 , 36 , 44 , 49 , 53 , 59 - 61 , 65 , 67 , 77 male breast, 58 cervix, 24 , 50 ovary, 23 , 42 , 45 endometrium, 33 prostate, 7 , 34 , 43 , 64 penis, 47 colorectum, 12 , 15 , 22 , 28 , 40 , 48 , 55 , 57 , 66 , 73 lung, 10 , 11 , 16 , 20 , 25 , 41 , 56 head and neck, 31 ...…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies examined the underlying causes of educational and socio-economic inequalities in breast cancer survival: 8 from Europe, 9 , 13 , 18 , 30 , 32 , 36 , 44 , 49 5 from the US, 59 - 61 , 65 , 67 2 from New Zealand 76 , 77 and 1 from Australia. 74 Studies from Switzerland, Italy, Ireland, New Zealand and Australia applying the difference method reported consistent findings that stage at diagnosis, other tumor characteristics, method of detection or presentation (symptomatic, screening, incidental, unknown), and receiving suboptimal treatment and sector of care (private or public) only partly explained the observed socio-economic inequalities in breast cancer survival.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that differences in survival by deprivation are evident among both women whose cancer was screen-detected and those not screen-detected [ 36 ] and that these differences are not entirely explained by adjustment for stage of disease and treatment received [ 39 ]. In those analyses we made corrections for potential biases due to lead time [ 40 ] and over-diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom there have been national policies aimed at reducing inequalities ( Department of Health, 2000 ; Department of Health, 2011 ), but any changes have been minor ( Rachet et al , 2009 ; Rachet et al , 2010 ). Part of the observed differences in survival between socio-economic groups can be explained by stage at diagnosis ( Rutherford et al , 2013 ; Morris et al , 2016 ).…”
mentioning
confidence: 99%